SISTEM INFORMASI KELUHAN PELANGGAN BERBASIS MOBILE PADA PDAM KOTA MAGELANG - Al Munawar, Habib Riziq; Santoso, Kartika Imam; Febriani, Yeza (STMIK BINA PATRIA, 2024)
The aim of this research is to be able to design and build a Mobile-Based Customer Complaint Information System at PDAM Magelang City, and to find out the impact of implementing a customer complaint information system at PDAM Magelang City. The research methodology used is a software engineering approach. Meanwhile, the system development method uses Waterfall. The stages are Requirements Definition, System and Software Design, Implementation and Unit Testing, Implementation and Unit Testing, Operation and Maintenance. The system design used in this research is modeling using Data Flow Diagrams (DFD). The result of this research is a mobile-based customer complaint information system at PDAM Magelang City. And the impact of implementing this customer complaints system is that PDAM Kota Magelang can receive customer complaints in real time with a score of 84.4%, customers can submit complaints anytime and anywhere via cellphone or Android-based gadget.Keywords: Customer Complaint Information System,Â Magelang City, PDAM, Mobile, Waterfall.